Goppa and Srivastava codes over finite rings - De Andrade, Antonio Aparecido [UNESP]; Palazzo, Reginaldo (My University, 2005)
Goppa and Srivastava codes over arbitrary local finite commutative rings with identity are constructed in terms of parity-cleck matrices. An efficient decoding procedure, based on the modified Berlekamp-Massey algorithm, is proposed for Goppa codes.
Keywords: Goppa code; Srivastava code